Correlation Between Different Traits Of Aromatic Rice (Oryza Sativa L.) And Their Cause-Effect Relationship (Applied Biological Research, 2012)
The present study was undertaken with the objective to study the  correlation between different traits of aromatic rice and cause-effect  relationship. Thirty aromatic rice genotypes were grown at Rice  Research field, RAU, Pusa, Bihar, India in four environments (2 dates of  sowing for 2 years i.e. kharif 2008 and 2009). Observations on 21  morphophysiological and quality traits were recorded. Grain yield  showed significant but positive association with effective tillers plant-1,  filled grains panicle-1, grain weight panicle-1, leaf area index and harvest  index. The genotypic and phenotypic correlation showed similar trend  of association, except for a few combinations. The component traits of  grain yield in aromatic rice genotypes were harvest index, grain weight  panicle-1, effective tillers plants-1, filled-grain panicle-1and leaf area  index. The selection based on these component traits may increase the  grain yield in aromatic rice. Leaf area index may be a preferable  selection criterion due to its high positive indirect effects via kernel  length towards yields along with other component characters with high  direct effects towards yield.
Keywords: Aromatic rice; correlation; path coefficient analysis